Special weapons and tactics teams in Canadian policing: legal, institutional, and economic dimensions - Roziere, Brendan (Policing and society, 2020)
Despite extensive social science analysis of special weapons and tactics (SWAT) team deployment across the United States, the phenomenon in Canada has been overlooked. Drawing from data on deployments disclosed under freedom of information (FOI), legal decisions, and media data, our findings reveal that the use of SWAT teams have escalated in many major Canadian cities. Public police now deploy SWAT teams across Canada for routine law enforcement activities such as warrant work, traffic enforcement and other routine tasks, as well as responding to mental health crises and domestic disturbances. We then develop three sociological explanations for the rise and current use of SWAT teams in Canadian policing. We draw from sociologies of law, institutionalism and institutional effects, and field/capital. This paper concludes with reflections on the implications for public policing and avenues for future research on police militarisation in Canada and beyond.